American Football and COVID-19: reducing on-field exposures to respiratory particles - Langon, T. N.; Hill, W. C.; Rogers, M. B.; Goforth, M.; MacCuspie, R. I.; Duma, S. M.; Hull, M. S. (The Sport Journal, 2021)
American football poses unique challenges to protecting the health of athletes both on and off the field. While off-field activities likely pose the greatest risk of COVID-19 transmission among members of the same team, on-field activities may pose transmission risks from one team to another. The findings of this study suggest that, when used in well-ventilated outdoor environments, helmet modifications combining upper and lower visors may help reduce on-field respiratory transmission risks with relatively minimal effects on athletic performance. These findings may offer practical insights to team physicians and athletic trainers as they seek strategies to protect athletes against on-field transmission of COVID-19 in the weeks and months ahead.